How far can we call tiktok shop live streaming a personal touchpoint? - Vindalia Annisa; Juni Alfiah Chusjairi (Jurnal Mantik, 2023)
To analyze consumer behaviours of TikTok Shop live streaming, specifically the Gen Z generation towards emotional factors and to see its potential to become a personal touchpoint. Qualitative research was used to conduct the research, followed by interviewing three informants chosen from convenience sampling. The interview process took time from September until October 2022 using Zoom and filling out questions on the documents. The informants tend to use TikTok as the search engine, but when it comes to the live streaming part, they likely utilize the price reduction or vouchers to pay their orders with lower prices, hence there is no such thing as an emotional factor or interpersonal relationship in the buying activity on the platform. Conduct both quantitative and qualitative research as part of the product development process in order to maintain users’ attention towards TikTok Shop, especially the live streaming shopping feature and continue innovating to attract users and not make them rely on the price or promotion.